PENGARUH LEVERAGE TERHADAP INCOME SMOOTHING DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2018-2020 - Arifah, Ila Nur; Wahyuni, Ika; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2022)
The rapid growth in the banking sector in recent years has presented a serious challenge to the company's management. The management is indirectly forced to show the best performance of the company. High leverage can affect profitability because the higher the leverage value, the smaller the company's profitability, so when profitability is small, the company can carry out income smoothing activities to stabilize the profits listed in the financial statements. This can be a source of reference for outside banks to invest funds in the form of savings and creditors who are interested in making loans to banks so that they can increase the company's income. The purpose of this study is to determine how influence Leverage has on Income smoothing through the Profitability variable. The population in this study are banking sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sampling technique used is purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Leverage has a significant negative effect on Profitability, Leverage has a significant negative effect on Income smoothing, Profitability has a negative but not significant effect on Income smoothing. The results of the indirect effect hypothesis test show that the Leverage variable on Income smoothing through Profitability has a positive but not significant effect.